Diseño de prácticas virtuales de automatización basado en la conectividad entre Factory I/O Y Codesys (2020)
In this document, the connectivity between the Factory iIO and Codesys programs is developed in order to provide a tool for virtual automation practices, since the Factory I / O program is a platform that has 3D industrial processes that allow practicing in an almost real way, without problems when having programming errors, allowing the student to dedicate themselves to programming without complications if they have faults in the testing process, in addition, online modifications can be made, and this is something This is important in the industry, since after carrying out automation, an industrial process must be developed. The Codesys software is one of the tools that is based on the IEC-61131-3 standard that establishes the programming language of the PLCs, it also includes many of these different types of language, making it very complete and relevant for teaching automation.